Static and dynamic analysis of a pump impeller with a balancing device. Part I: Static analysis - Kundera, Czesław; Martsynkowskyy, Volodymyr A. (Zielona Góra: Uniwersytet Zielonogórski)
This part of the work presents the design and static analysis of an impeller for a single-stage pump. The impeller is directly connected with a balancing device. The impeller needs to have a properly designed system of longitudinal and lateral clearances on both sides. With the simplifying assumptions concerning the flow and distribution of pressure in the longitudinal and lateral clearances, the static analysis involved deriving relationships between the impeller geometry and the basic performance parameters of the pump. A numerical example was used to show the calculation procedure of static characteristics for the predetermined parameters.
Keywords: pump impeller; balance device; static analysis